2012
DOI: 10.1186/1423-0127-19-25
|View full text |Cite
|
Sign up to set email alerts
|

Decreased GABA receptor in the cerebral cortex of epileptic rats: effect of Bacopa monnieri and Bacoside-A

Abstract: AbstactBackgroundGamma amino butyric acid (GABA), the principal inhibitory neurotransmitter in the cerebral cortex, maintains the inhibitory tones that counter balances neuronal excitation. When this balance is perturbed, seizures may ensue.MethodsIn the present study, alterations of the general GABA, GABAA and GABAB receptors in the cerebral cortex of the epileptic rat and the therapeutic application of Bacopa monnieri were investigated.ResultsScatchard analysis of [3H]GABA, [3H]bicuculline and [3H]baclofen i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…Three isoform of GABA receptors have been recognized. GABA A and GABA C receptors are ligand-gated chloride (Cl -) ionotropic receptors whereas GABA B receptor is G protein coupled receptor [29,30] . It is well documented that ICV injection of GABA A receptor agonist increases food consumption [31][32][33][34] .…”
Section: Gabamentioning
confidence: 99%
“…Three isoform of GABA receptors have been recognized. GABA A and GABA C receptors are ligand-gated chloride (Cl -) ionotropic receptors whereas GABA B receptor is G protein coupled receptor [29,30] . It is well documented that ICV injection of GABA A receptor agonist increases food consumption [31][32][33][34] .…”
Section: Gabamentioning
confidence: 99%
“…Studies of Brahmi for epilepsy in the Caenorhabditis elegans model showed that its active constituent Baccoside A suppressed epileptic-like seizures/convulsions induced by exposure to higher temperature [109]. Matthew and his group have consistently shown that B. monnieri reverses the decrease in GABA receptors in the cerebellum, striatum, hippocampus, and cerebral cortex and associated behavioral and motor deficits in epileptic rats [110][111][112][113][114][115]. Other studies have also shown that B. monnieri normalizes glutamate-mediated excitotoxicity in epilepsy, evidenced by upregulation of 5-HT2C, NMDA, and IP3 receptors in the cerebellum, hippocampus, and cerebral cortex and associated behavioral, cognitive, and motor changes in epileptic rats [116][117][118].…”
Section: Acorus Calamus L (Vacha)mentioning
confidence: 97%
“…The active constituents of Bacopa monnieri extracts are triterpene bacosides or bacopasides that are structurally similar to the ginsenosides [ 208 , 209 ]. Whilst the exact mechanisms by which Bacopa modulates brain function remain unclear, animal research suggests interactions with the acetylcholine, opioid and GABA neurotransmitter systems [ 210 214 ] and the HPA axis [ 215 ].…”
Section: Terpenesmentioning
confidence: 99%